Preparatory Questions: Solutions To Tutorial 2
Preparatory Questions: Solutions To Tutorial 2
Preparatory Questions: Solutions To Tutorial 2
Solutions to Tutorial 2
MATH1001: Differential Calculus Summer School, 2008
Web Page: http://www.maths.usyd.edu.au/u/UG/SS/SS1001/
Preparatory questions
1. Express the following complex numbers in Cartesian form:
(a) (2 − i) + (3 + 5i)
Solution: (2 − i) + (3 + 5i) = (2 + 3) + i(−1 + 5) = 5 + 4i.
(b) (2 − i) − (3 + 5i)
Solution: (2 − i) − (3 + 5i) = (2 − 3) + i(−1 − 5) = −1 − 6i.
(c) (2 − i)(3 + 5i)
Solution: (2 − i)(3 + 5i) = 6 + 10i − 3i − 5i2 = 11 + 7i.
2−i
(d)
3 + 5i
2−i (2 − i)(3 − 5i) 6 − 10i − 3i + 5i2 1 − 13i
Solution: = = = .
3 + 5i (3 + 5i)(3 − 5i) 32 + 52 34
2. Write down the modulus and principal argument of the following complex numbers:
(a) i
Solution: In the general case, z = x + iy = r(cos θ + i sin θ ), the modulus of z is |z| =
r = x2 + y2 and the arguments of z, denoted arg z, are θ + 2kπ , k ∈ Z, where one can
p
calculate θ from cos θ = x/r and sin θ = y/r, being careful with the choice of quadrant.
The principal argument, denoted Arg z, is the value of θ in the range, −π < θ ≤ π .
For the particular case z = i, we can read off r = 1 and θ = π /2 by inspection. Hence,
|i| = 1 and Arg i = π /2.
(b) 1 + i
√ √ √
Solution:√ Here, x = y = 1, so r = 12 + 12 = 2 and cos θ = sin θ = 1/ 2 . Hence,
|1 + i| = 2 and Arg(1 + i) = π /4.
(c) 1 − i
Solution: This is the complex conjugate of the previous√example. The modulus stays the
same while the argument changes sign. Hence, |1 − i| = 2 and Arg(1 − i) = −π /4.
(d) −6i
Solution: By inspection, | − 6i| = 6 and Arg(−6i) = −π /2.
√
(e) 1 + 3 i
√ √
Solution:
√ Here, x = 1√and y = 3 . Hence, r√= 1 + 3 = 2 and cos θ = 1/2 and sin θ =
3/2. This gives |1 + 3 i| = 2 and Arg(1 + 3 i) = π /3.
√
(f) − 3 − i
√ √ √
Solution: Here, x = − 3 and y = −1. Hence, r = 3 + 1 = 2 and cos √ θ = − 3/2
θ = −1/2. The argument θ lies in the third quadrant. We get | − 3 − i| = 2 and
and sin√
Arg(− 3 − i) = −5π /6.
Copyright
c 2008 The University of Sydney 1
3. Find the exact complex solutions to the following equations:
(a) z2 + 4 = 0
Solution: z2 = −4 implies two roots, z = ±2i.
(b) z2 + z + 1 = 0
√ √
Solution: The quadratic formula gives z = (−1 ± 1 − 4 )/2 = (−1 ± i 3 )/2.
(c) z2 + 2z + 4 = 0
√ √ √
Solution: Similarly, z = (−2 ± 4 − 16 )/2 = (−2 ± 2i 3 )/2 = −1 ± i 3 .
Questions to do in class
4. Write down polar forms for the following complex numbers (using your answers to Problem 2 or
otherwise):
(a) i
Solution: i = cos(π /2) + i sin(π /2)
(b) 1 + i
√
2 cos(π /4) + i sin(π /4)
Solution: 1 + i =
(c) 1 − i
√
2 cos(−π /4) + i sin(−π /4) .
Solution: 1 − i =
5. Convert the following complex numbers into Cartesian form a + bi where a and b are real:
(a) 2 cos(π /4) + i sin(π /4)
√ √ √
Solution: 2 cos(π /4) + i sin(π /4) = 2 + 2 i = 2 (1 + i).
(b) −4 cos(π /3) + i sin(π /3)
√ √
Solution: −4 cos(π /3) + i sin(π /3) = −2 − 2 3 i = −2(1 + i 3 ).
(c) cos(π /2) + i sin(π /2) cos(π /3) + i sin(π /3) cos(π /6) + i sin(π /6)
Solution:
cos(π /2) + i sin(π /2) cos(π /3) + i sin(π /3) cos(π /6) + i sin(π /6)
2
2 cos(π /6) + i sin(π /6)
z
=
w 2 cos(π /3) + i sin(π /3)
= cos π /6 − π /3 + i sin π /6 − π /3
= cis −2π /3 ,
1 1 π π
= cos + i sin .
z 8 6 6
7. Find the indicated power, expressing your final answer in Cartesian form:
(a) (1 − i)24
Solution:
√ 24
(1 − i)24 = 2 cos(−π /4) + i sin(−π /4)
= 212 cos(−6π ) + i sin(−6π )
= 212
= 4096.
√
(b) (1 + 3 i)7
Solution:
√ 7
(1 + 3 i)7 = 2 cos(π /3) + i sin(π /3)
= 27 cos(7π /3) + i sin(7π /3)
= 63 i
= 216i.
3
8. Solve the following equations (giving your answers in polar form, ‘cis’ notation recommended)
and sketch the solutions in the complex plane:
(a) z5 = 1
Solution: We use the shorthand notation cis θ = cos θ + i sin θ throughout this question.
z5 = 1 if and only if z = 1, cis(2π /5), cis(4π /5), cis(6π /5) or cis(8π /5). The solutions
lie equally spaced on the unit circle (regular pentagon).
i
Using the principal arguments, we have z = 1 = cis(0), cis(2π /5), cis(4π /5),
cis(−4π /5) and cis(−2π /5).
(b) z6 = −1
Solution: z6 = −1 = cis π if and only if z = cis(π /6), cis(π /2) = i, cis(5π /6),
cis(7π /6), cis(3π /2) = −i or cis(11π /6).
i
Using the principal arguments, we have z = cis(π /6), cis(π /2) = i, cis(5π /6),
cis(−5π /6), cis(−π /2) = −i and cis(−π /6).
√
(c) z3 = 4 − 4 3 i
√ √ √ √
Solution: |4 − 4 3 i| = 4 1 + 3 = 8 and arg(4 − 4 3 i) = −π /3. So if z3 = 4 − 4 3 i =
8 cis(−π /3), then we will have three solutions for z and
−π /3 + 2π k
z = 81/3 cis for k = 0, 1, 2
3
2 cis(−π /9), (k = 0),
= 2 cis(5π /9), (k = 1),
2 cis(11π /9), (k = 2).
Using the principal arguments, we have z = 2 cis(−π /9), 2 cis(5π /9) and 2 cis(−7π /9).
In the complex plane the points are as follows:
2i
(d) z4 = 9i
Solution: |9i| = 9 and arg(9i) = π /2. So if z4 = 9i = 9 cis(π /2), then we will have four
4
solutions for z4 = 9i and
π /2 + 2π k
z = 91/4 cis for k = 0, 1, 2, 3
√ 4
3 cis(π /8), (k = 0),
√3 cis(5π /8),
(k = 1),
= √
3 cis(9π /8), (k = 2),
√3 cis(13π /8), (k = 3).
√ √ √
√the principal arguments, we have z = 3 cis(π /8), 3 cis(5π /8), 3 cis(−7π /8)
Using
and 3 cis(−3π /8). In the complex plane
√ the points are as follows:
3i
√
3
10. Solve the following equations (giving your answers in polar form, ‘cis’ notation recommended)
and sketch the solutions in the complex plane:
(a) z3 + i = 0
Solution: z3 = −i = cis(−π /2) if and only if z = cis(−π /6), cis(π /2) = i or
cis(−5π /6).
i
√ √
(b) z4 = 8 2 + 8 2 i
√ √
Solution: z4 = 8 2 + 8 2 i = 16 cis(π /4) if and only if z = 2 cis(π /16), 2 cis(9π /16),
2 cis(17π /16) or 2 cis(25π /16).
5
2i
Using the principal arguments, we have z = 2 cis(π /16), 2 cis(9π /16), 2 cis(−15π /16)
and 2 cis(−7π /16).
(c) z5 + z3 − z2 − 1 = 0, given that z = i is a root.
Solution: z5 + z3 − z2 − 1 = 0 has the complex conjugate pair z = ±i as solutions, so
(z − i)(z + i) = z2 + 1 is a factor of the left-hand side, yielding
(z2 + 1)(z3 − 1) = 0.
Hence, the five solutions are ±i = cis(±π /2) and the cube roots of 1 which are cis(0) = 1
and cis(±2π /3).
i
Now (using your answers to Problem 3) write down all complex cube roots of 1 and 8. If a is any
real number, can you write down easily all complex cube roots of a3 ?
√ √
Solution: The complex cube roots of 1 are 1, (−1 + i 3 )/2 and (−1 − i 3 )/2; the latter two
cis(2π /3) and
solutions follow by solving the quadratic equation z2 + z + 1 = 0 or√by evaluating√
cis(−2π /3). . Similarly, the complex cube roots of 8 are 2, −1√+ i 3 and −1 − i √ 3 . If a is any
3
real number then the complex cube roots of a are a, a(−1 + i 3 )/2 and a(−1 − i 3 )/2.
12. The square roots of a complex number can be calculated directly in the Cartesian representation.
√
Use the radical notation z to denote the principal value of the square root of z. Every complex
number, including zero, has a unique principal square root. In addition, all nonzero complex
numbers have a non-principal square root, which is the negative of the first. Suppose that z = x+iy
√
and z = w = u + iv. The principal square root can be identified by the property that u ≥ 0, and,
if u = 0, then v ≥ 0.
√
(a) Calculate 21 − 20i by equating real and imaginary parts in the expression (u + iv)2 =
21 − 20i and solving for u and v, with u > 0. Check your answer by squaring.
Solution: Start with (u + iv)2 = u2 − v2 + 2iuv = 21 − 20i. This gives two real-variable
equations, u2 − v2 = 21 and 2uv = −20. Thus v = −10/u. Substituting into the first
6
equation gives
100
u2 − = 21,
u2
u4 − 21u2 − 100 = 0,
(u2 − 25)(u2 + 4) = 0,
u2 = 25 (since u2 cannot be −4),
u=5 (since u is nonnegative).
7
(c) Find the two roots of the quadratic equation,
z2 + (3 + 4i)z − 7 + 11i = 0.
2
Solution: The two solutions of any quadratic equation √ az + bz+ c = 0 with real or
2
complex coefficients and a 6= 0 is given by z = − b ± b − 4ac /(2a). Here, a = 1,
b = 3 + 4i and c = − 7 + 11i. Hence, the roots of the given quadratic equation are
p
− 3 − 4i ± (3 + 4i)2 − 4(− 7 + 11i)
z=
√ 2
− 3 − 4i ± 9 + 24i − 16 + 28 − 44i
=
√ 2
− 3 − 4i ± 21 − 20i
=
2
− 3 − 4i ± (5 − 2i)
= (from the result of part (a))
2
= 1 − 3i and − (4 + i).
u2 − v2 = 21 (r + x) − 21 (r − x)
= x,
as required. Also,
q q
2uv = 2ε (y) 2 (r + x) 12 (r − x)
1
q
= 2ε (y) 14 (r2 − x2 )
q
= ε (y) (x2 + y2 ) − x2
= ε (y) y2
p
= ε (y)|y|
=y (from the definition of ε (y)),
as required. This completes the proof that u + iv is one of the square roots of x + iy. To
conclude, we need to show that it is the principal square root. Observe that u ≥ 0 because
it is the nonnegative square root of a nonnegative real number. The only way that u can be
zero is if x ≤ 0 and y = 0. But, in that case, v ≥ 0 because we defined ε (0) = +1. Hence,
the given square root is indeed the principal square root in all cases.